About the place of Karluks in the political life of the Turkic Khaganate - Annakurbanov Rejepguly Haknazarovich (Studia Humanitatis)
Some historical events and episodes still remain poorly understood despite the fact that the history of the Turkic Khaganate has been well studied by orientalists. This applies, among other things to the participation of some tribes in the political life of the State. The article examines the place of the Karluks in the history of the Turkic Khaganate. It also analyses the reasons for the struggle of the eastern Karluks against the recreated Eastern Turkic Khaganate, as well as the features of the political struggle of the Western Karluks.